2022
DOI: 10.1021/acsnano.2c02810
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Intercalation–Conversion Site Supported Ultrathin 2D Mesoporous SnO2/SnSe2 Hybrid as Bifunctional Polysulfide Immobilizer and Lithium Regulator for Lithium–Sulfur Chemistry

Abstract: The practical application of lithium–sulfur batteries is impeded by the polysulfide shuttling and interfacial instability of the metallic lithium anode. In this work, a twinborn ultrathin two-dimensional graphene-based mesoporous SnO2/SnSe2 hybrid (denoted as G-mSnO2/SnSe2) is constructed as a polysulfide immobilizer and lithium regulator for Li–S chemistry. The as-designed G-mSnO2/SnSe2 hybrid possesses high conductivity, strong chemical affinity (SnO2), and a dynamic intercalation–conversion site (Li x SnSe2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
47
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(47 citation statements)
references
References 52 publications
0
47
0
Order By: Relevance
“…A high areal capacity of around 7.5 mAh cm –2 was attained at 0.05 C with clear discharge plateaus (Figure h and Figure S26a). After cycling at 0.2 C for 50 cycles, the areal capacity of around 4.9 mAh cm –2 was maintained, which is higher than that of the commercial Li-ion batteries (4 mAh cm –2 ) . Two tandem coin cells can power the light-emitting diode and electric fan (Figure S26b and Figure h).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…A high areal capacity of around 7.5 mAh cm –2 was attained at 0.05 C with clear discharge plateaus (Figure h and Figure S26a). After cycling at 0.2 C for 50 cycles, the areal capacity of around 4.9 mAh cm –2 was maintained, which is higher than that of the commercial Li-ion batteries (4 mAh cm –2 ) . Two tandem coin cells can power the light-emitting diode and electric fan (Figure S26b and Figure h).…”
mentioning
confidence: 97%
“…After cycling at 0.2 C for 50 cycles, the areal capacity of around 4.9 mAh cm −2 was maintained, which is higher than that of the commercial Li-ion batteries (4 mAh cm −2 ). 42 Two tandem coin cells can power the light-emitting diode and electric fan (Figure S26b and Figure 4h). With a lower N/P ratio around 3.8 (Figure S27), the Ni−Fe−NC/S cathode with 5 mg cm −2 areal sulfur loading retains a reversible capacity of 550 mAh g −1 after 60 cycles at 0.5 C under lean electrolyte condition (6 μL mg −1 ).…”
mentioning
confidence: 99%
“…The active sites of transition metal catalysts usually have an affinity for polysulfides, which results in a large amount of Li 2 S accumulating and reducing the oxidation kinetics during charging. This can be remedied through, in addition to the common structure modulation, the construction of heterogeneous structures, which can also enhance the bidirectional redox kinetics of Li–S batteies. In contrast to individual TMCs, the heterogeneous structures designed by interface engineering combine the advantages of different materials to create synergistic effects that result in good physicochemical properties. Recently, an increasing number of researchers found that the heterostructures could accelerate charge transfer and promote the bidirectional sulfur reaction kinetics to significantly improve the electrochemical performance of Li–S batteries. Table shows the electrochemical performance of heterostructures as the sulfur host/separator modifier in Li–S batteries.…”
Section: Tmcs In Li–s Batteriesmentioning
confidence: 99%
“…The two main challenges associated with Li-S batteries are the poor conductivity of elemental sulfur and nal Li 2 S/Li 2 S 2 components as well as the shuttle effect of soluble lithium polysuldes produced during the multi-step reduction, which inevitably leads to slow conversion kinetics and rapid capacity decay of the batteries. 8 In addition, Li-S batteries are plagued by the large volume change and uncontrolled growth of lithium dendrites. [9][10][11] These features prevent LSBs from being commercially applied.…”
Section: Introductionmentioning
confidence: 99%